Trichosanthes pericarpium Aqueous Extract Enhances the Mobilization of Endothelial Progenitor Cells and Up-regulates the Expression of VEGF, eNOS, NO, and MMP-9 in Acute Myocardial Ischemic Rats - Fu, Nini; Li, Hang; Sun, Jingchang; Xun, Liying; Gao, Dongmei; Zhao, Qitao (Frontiers in Physiology, 2018)
Trichosanthes pericarpium (TP) had been widely used to cure patients of cardiovascular disease for two thousand years in China. This study aims to extend our previous work, to reveal the mechanism underlying the protective effect of TP on acute myocardial ischemia (AMI). We hypothesized that TP may display its protective effect on AMI by promoting the mobilization of endothelial progenitor cells (EPCs), and by up-regulating the expression or secretion of vascular endothelial growth factor (VEGF), endothelial nitric oxide syntheses (eNOS), nitric oxide (NO) and matrix metalloproteinase 9 (MMP-9) in AMI rats. To confirm this hypothesis, we treated AMI model rats with intragastrical administration of TP aqueous extract (TPAE), and performed experiments to observe the change in the number of CEPCs per ml blood, the expression of VEGF, eNOS, NO and MMP-9 in myocardial tissue and their plasma content or activity in these rats. Rats in each group were randomly subdivided into seven subgroups. At day 1~7 following AMI modeling, rats in 1~7 subgroups were selected to be phlebotomized from their celiac artery after being anesthetized by chloral hydrate respectively. We found that, in 7 days after AMI, compared with the AMI mode rats, in rats treated by TPAE, the CEPCs counts, the expression of VEGF, eNOS, NO and MMP-9 in myocardial tissue and their plasma concentration or activity increased more rapidly, remained higher level (P<0.05 or P<0.01). Our results showed that, in AMI rats, the TPAE could observably promote the mobilization of EPCs and notably up-regulate the expression of VEGF, eNOS, NO and MMP-9 in myocardium and their plasma level; this Chinese herbal medicine might regulate EPCs mobilization by increasing the expression or secretion of VEGF, eNOS, NO and MMP-9 in the myocardium of AMI rats.